Psychometric evaluation of the Czech Beck Depression Inventory-II in a sample of depressed patients and healthy controls - Ociskova, Marie; Prasko, Jan; Kupka, Martin; Marackova, Marketa; Latalova, Klara; Cinculova, Andrea; Grambal, Ales; Kasalova, Petra; Krnacova, Barbora; Kubinek, Radim; Sigmundova, Zuzana; Tichackova, Anezka; et al. (Neuro endocrinology letters, 2017)
OBJECTIVE: The goal of this study was to explore reliability and validity of the Czech revised Beck Depression Inventory (BDI-II) and to identify the best cut-off for a correct identification of a potentially depressed individual. METHOD: Two groups of adult participants entered the study. The first group consisted of 177 patients with depression (F32x or F33x according to the ICD-10). Furthermore, there were 767 healthy controls. Each participant filled in BDI-II. A part of the patients also completed the Beck Anxiety Inventory (BAI), the Dissociative Experiences Scale (DES), and the subjective Clinical Global Impression scale (CGI). A part of the controls filled in the Adult Dispositional Hope Scale (ADHS) and the Satisfaction with Life Scale (SWLS). RESULT: The average patients' BDI-II score was 30.8±10.3, the mean controls' score was 7.2±6.8. The internal consistency of the inventory was excellent (the ordinal alpha coefficient was 0.90 for the patients and 0.93 for the controls). The stability in time, measured two weeks apart, was also good (intra-class correlation coefficient r=0.83 for the patients and 0.77 for the controls). The exploratory factor analysis of the patients showed a three-factor solution, while the analysis of the controls' data identified two factors. As expected, BDI-II significantly positively correlated with BAI, DES, and CGI and was negatively connected to ADHS and SWLS. The cut-off score with the best sensitivity and specificity was 17. CONCLUSION: The Czech BDI-II shows adequate psychometric characteristics.
Keywords: Male; Factor Analysis, Statistical; lidé středního věku; Psychiatric Status Rating Scales; senzitivita a specificita; osobní uspokojení; Humans; Reproducibility of Results; depresivní poruchy; Middle Aged; reprodukovatelnost výsledků; Česká republika; mužské pohlaví; Czech Republic; Depressive Disorder; Female; mladiství; deprese; psychometrie; Psychometrics; ženské pohlaví; mladý dospělý; Adult; Young Adult; Sensitivity and Specificity; Translations; Depression; Adolescent; dospělí; lidé; překlady; Personal Satisfaction; psychiatrické posuzovací škály; faktorová analýza statistická